Artificial neural networks as regulatory devices in digital capitalism - Alarcón, Sara (2025)
This paper aims to analyze the role of artificial neural networks in contemporary surveillance and control dynamics, with a particular focus on the epistemic opacity that characterizes them. It argues that, although these technologies have been developed to optimize data extraction in digital capitalism, their opaque and decentralized nature has transformed surveillance into a more subtle and imperceptible phenomenon. Based on this analysis, it is suggested that ANNs can be interpreted within the Foucauldian framework as an update to disciplinary and biopolitical dispositives, expanding the ways in which power is exercised over individuals and populations.